2019
DOI: 10.15640/jaes.v8n1a17
|View full text |Cite
|
Sign up to set email alerts
|

Farmer’s Prioritization and Adoption of Climate-Smart Agriculture (CSA) Technologies and Practices

Abstract: Climate change affects seriously household food security, especially in sub-Saharan Africa where agriculture is still using traditional methods of farming systems. As strategies against the impact of climate change and way to increase agricultural production, several Climate-Smart Agriculture (CSA) technologies and practices were introduced and experimented at sub-regional and national levels in Niger. The purpose of this study is to prioritize these technologies and practices using participatory assessment ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Some of the studies in Niger found out several adaptation strategies to climate change have been adopted (Asfawa et al, 2016; Moussa & Abasse, 2020), such as organic fertilizer, mulching, fallows, agroforestry and manure applications. Standard CSAT adopted by farmers are improved crop varieties, zaï and halfmoon practices and planting of trees (Zakari et al, 2019). The utilisation of CSA in Niger can double cereals yields in the degraded lands (Lamanna et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some of the studies in Niger found out several adaptation strategies to climate change have been adopted (Asfawa et al, 2016; Moussa & Abasse, 2020), such as organic fertilizer, mulching, fallows, agroforestry and manure applications. Standard CSAT adopted by farmers are improved crop varieties, zaï and halfmoon practices and planting of trees (Zakari et al, 2019). The utilisation of CSA in Niger can double cereals yields in the degraded lands (Lamanna et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Rainfed agriculture is still dominant among farmers across the continent. Conventional farming systems in Sub-Saharan Africa (SSA) have impacted food security in households (Zakari et al, 2019). The Sahara and Sahel have recorded the highest increase in average annual and seasonal surface temperature of 1-3℃ beginning from the mid-1970s (CDKN, 2022; IPCC, 2022), and this is projected to be higher in the West African Sahel than the global warming average of 1.5℃ in 2021-2040, 2℃ in 2041-2060 and 3℃ in 2081-2100.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations